2018
DOI: 10.16955/bitkorb.333371
|View full text |Cite
|
Sign up to set email alerts
|

Some notes to morphological and bioacoustics characteristics of Cicadatra hyalina (Fabricius, 1798) (Cicadoidea: Cicadidae) according to samples collected from different parts of Turkey

Abstract: Some notes to morphological and bioacoustics characteristics of Cicadatra hyalina (Fabricius, 1798) (Cicadoidea: Cicadidae) according to samples collected from different parts of Turkey Türkiye'nin farklı bölgelerinden toplanan örneklerle Cicadatra hyalina (Fabricius, 1798) (Cicadoidea: Cicadidae)'nın morfoloji ve biyoakustik karakterleriyle ilgili bazı notlar INTRODUCTION Abbas MOL a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is repeated regularly, lasting between 640-8952±651ms. Echemes are separated by intervals between 232-704±149 ms. Echemes consist of two connected pulses of 2-3 ms length, separated by intervals between 14-16 ms (Mol 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is repeated regularly, lasting between 640-8952±651ms. Echemes are separated by intervals between 232-704±149 ms. Echemes consist of two connected pulses of 2-3 ms length, separated by intervals between 14-16 ms (Mol 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Frequency parameters of the calling song are characerized by a wide range with distinct peaks (Popov 1975;Boulard 1995). Mol (2018) measured a frequency range from from 10248 to 16760…”
Section: Tibicen Plebejus (Scopoli 1763)mentioning
confidence: 99%
“…sirintaylan sp. n. can be differentiated from O. tibialis using the following characters: (i) the pseudoparameres are short, hardly visible, and not extending median lope of uncus (in O tibialis the pseudoparameres are long, divergend and much longer than median lobe of uncus), (ii) pronotal collar, its lateral part, anterior and posterior edge of pronotum yellow (in O. tibialis blackish), (iii) terga 3-7 black with yellowish red borders (in O.tibialis without), (iv) ulnar cell I is 1.5-1.95 times longer than apical cell I in male, 2-2.5 in female (in O. tibialis 1.25-1.42 in male, 0.85-1 in female), (v) hind wings with 5 apical cells in male (in O. tibialis 6), (vi) ovipositor length 4.2-6.2 mm (in O. tibialis 3.93-4.68), and (vii) pygofer inner teeth opposite to claspers (in O. tibialis not opposite) (Gogala & Drosopoulos 2006;Gogala et al, 2017;Mol, 2017).…”
Section: Morphological Diagnosismentioning
confidence: 99%
“…Generally according to the results of the morphologically studies conducted at different time intervals, it is shown that 29 species belonging to Cicadidae family are distributions and nine of these are endemic in Turkey (Nast, 1972;Lodos & Kalkandelen, 1981;Duffels & Laan, 1985;Demir, 2007;Önder, Tezcan, Karsavuran, & Zeybekoğlu, 2011;Mol, 2020). Turkey, as well as the use of morphological characteristics of the species in taxonomic studies related to Cicadidae recently characterized, they also began to be used with acoustics characteristics (Zeybekoğlu et al, 2011;Mol, Zeybekoğlu, & Akyürek, 2013;Mol, 2017;2020). Acoustics characteristics are used to appoint the taxonomic intercourse, in addition to that, it has been prospective to differentiate the buddy species and to elucidate the taxonomic status of vernacular populations with petty morphological differences by song patterns among the Cicada species, such as Oligoglena (Gogala, Puissant, & Trilar, 2017;Mol, 2020).…”
Section: Introductionmentioning
confidence: 99%